2015
DOI: 10.4236/ajps.2015.67112
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of the Total Catechin Content in Oils Extracted from Seeds of Selected Tea (<i>Camellia sinensis</i> (L) O. Kuntze, Theaceae) Clones by RP-HPLC

Abstract: Catechins (flavan-3-ols) are polyphenolic plant secondary metabolites that have been strongly associated with a wide variety of beneficial health effects in vitro, in vivo and clinically. This study reports findings on the content of catechins in tea seed oil (TSO) extracted by Soxhlet extraction from seeds of different clones of Kenyan tea. Extraction of catechins from the crude oils was achieved by sequential liquid-liquid extraction (LLE) using methanol and quantified by reverse phase High Performance Liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Uoonlue and Muangrat () found that the saponin content of extracted Assam tea seed oil samples was in the range of 2,307.56–2,843.48 mg/100 g, using subcritical solvent extraction and Soxhlet extraction with isopropanol, hexane, and petroleum ether as solvents. Similarly, George, Moseti, Wanyoko, Kinyanjui, and Wachira () extracted oil from Camellia sinensis (L) O. Kuntze via Sohlet extraction, using hexane as solvent, and found a total flavonoid content of 9.0 × 10 −3 %. Wang, Zeng, Mar Contreras, and Wang () reported that the total concentrations of the phenolic compounds in C. sinensis, C. oleifera, and C. chekiangoleosa seed oils were in the range of 20.56–88.56 μg/g, with 76.2%–90.4% phenolic acids, 2.1%–9.7% catechins, and 4.2%–17.8% flavonoids.…”
Section: Resultsmentioning
confidence: 99%
“…Uoonlue and Muangrat () found that the saponin content of extracted Assam tea seed oil samples was in the range of 2,307.56–2,843.48 mg/100 g, using subcritical solvent extraction and Soxhlet extraction with isopropanol, hexane, and petroleum ether as solvents. Similarly, George, Moseti, Wanyoko, Kinyanjui, and Wachira () extracted oil from Camellia sinensis (L) O. Kuntze via Sohlet extraction, using hexane as solvent, and found a total flavonoid content of 9.0 × 10 −3 %. Wang, Zeng, Mar Contreras, and Wang () reported that the total concentrations of the phenolic compounds in C. sinensis, C. oleifera, and C. chekiangoleosa seed oils were in the range of 20.56–88.56 μg/g, with 76.2%–90.4% phenolic acids, 2.1%–9.7% catechins, and 4.2%–17.8% flavonoids.…”
Section: Resultsmentioning
confidence: 99%
“…Oil extraction was achieved using the solvent extraction method described by [6] [9]. A standard soxhlet apparatus set-up was used employing n-hexane as the solvent of choice and a solid:solvent ratio of 1:20.…”
Section: Oil Extractionmentioning
confidence: 99%
“…The tea plant is mainly cultivated for its prolific vegetative growth [1] from which different types of tea products have been processed viz., white tea [2] green tea [3], oolong tea, black tea [4] [5] among others. However, the tea plant also produces seeds from which high quality Tea Seed Oil (TSO), commonly referred to as camellia oil, can be pressed or extracted using suitable solvent(s) or solvent systems [6]- [9] with tea seed cake and husks as by-products. It is an edible, pale amber-green or golden vegetable oil and its physico-chemical properties as well as those of the above by-products have been investigated and [6] [9]- [13].…”
Section: Introductionmentioning
confidence: 99%
“…Tea is one of the most popular beverages worldwide, representing a significant part of the human diet. Derived from China, tea has been popular all around the world over the past 2000 years with its multiple health‐promoting effects . There are various kinds of teas in the market such as black tea, green tea, oolong tea, etc.…”
Section: Introductionmentioning
confidence: 99%